Effects of neoadjuvant chemotherapy for patients with obstructive colon cancer: A multicenter propensity score‐matched analysis (YCOG2101) - Kazuya Nakagawa; Atsushi Ishibe; Hiroki Ohya; Mayumi Ozawa; Yusuke Suwa; Jun Watanabe; Hirokazu Suwa; Kanechika Den; Koichi Mori; Masashi Momiyama; Koki Goto; Itaru Endo (Annals of Gastroenterological Surgery, 2024)
Abstract Aim Obstructive colon cancer is locally advanced colon cancer with poor prognosis. However, the effect of neoadjuvant chemotherapy (NAC) on obstructive colon cancer remains unclear. Therefore, this study aimed to investigate the safety and efficacy of NAC in patients with obstructive colon cancer. Methods From January 2012 to December 2017, we collected patient data for clinical stage II/III obstructive colon cancer at seven Yokohama Clinical Oncology Group (YCOG) institutions. The long‐term outcomes of the NAC and non‐NAC groups were analyzed retrospectively after adjusting for patients' background characteristics using propensity score matching. Results Among the 202 eligible patients, propensity score matching extracted 51 patients each for the NAC and non‐NAC groups. After matching, the groups showed no marked differences in the background factors. All the patients in the NAC group underwent diverting stoma construction. Nineteen patients (37.3%) experienced grade 3–4 adverse events during NAC. The incidence of postoperative complications was similar between groups. The 5‐year progression‐free survival rates were 75.8% in the NAC group and 63.0% in the non‐NAC group (p = 0.22, log‐rank test). The 5‐year overall survival rates were 88.5% in the NAC group and 78.8% in the non‐NAC group (p = 0.09, log‐rank test). Conclusion Although NAC was feasible for obstructive colon cancer after diverting stoma construction, its effects on long‐term outcomes could not be proven.